Development of Extracellular Vesicle Therapeutics: Challenges, Considerations, and Opportunities - Claridge, Bethany; Lozano, Jonathan; Poh, Qi Hui; Greening, David W. (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) hold great promise as therapeutic modalities due to their endogenous characteristics, however further bioengineering refinement is required to address clinical and commercial limitations. Clinical applications of EV-based therapeutics are being trialled in immunomodulation, tissue regeneration and recovery, and as delivery vectors for combination therapies. Native/biological EVs possess diverse endogenous properties that offer stability and facilitate crossing of biological barriers for delivery of molecular cargo to cells, acting as a form of intercellular communication to regulate function and phenotype. Moreover, EVs are important components of paracrine signalling in stem/progenitor cell-based therapies, are employed as standalone therapies, and can be used as a drug delivery system. Despite remarkable utility of native/biological EVs, they can be improved using bio/engineering approaches to further therapeutic potential. EVs can be engineered to harbor specific pharmaceutical content, enhance their stability, and modify surface epitopes for improved tropism and targeting to cells and tissues in vivo. Limitations currently challenging the full realisation of their therapeutic utility include scalability and standardisation of generation, molecular characterisation for design and regulation, therapeutic potency assessment, and targeted delivery. The fields’ utilisation of advanced technologies (imaging, quantitative analyses, multi-omics, labelling/live-cell reporters), and utility of biocompatible natural sources for producing EVs (plants, bacteria, milk) will play an important role in overcoming these limitations. Advancements in EV engineering methodologies and design will facilitate the development of EV-based therapeutics, revolutionising the current pharmaceutical landscape.